(untitled) (Journal of Economic Research & Business Administration, 2016)
In the article the current state and development trends of the chemical industry of Kazakhstan are analyzed. It is shown that the chemical industry is represented by a large complex of various branches and has a significant impact on the social and economic development of the country. For the development of the chemical industry of the country there are all the necessary prerequisites: rich natural resources and physical infrastructure for the production of chemical products. Analysis of the development of the chemical industry in the five years between 2009 and 2013 showed that the volume of chemical production increased more than twice. Increase in the production of chemical products is mainly due to the expansion and modernization of existing chemical plants.